Water in mineral processing - Kumar, Ombir (2016)
Water in Mineral Processing is an authoritative, first-of-its-kind resource that can help mining practitioners apply innovative water-use and purification technologies in the demanding years ahead. Water in Mineral Processing provides a comprehensive, state-of-the-art examination of this vital issue. A compilation of papers presented at the First International Symposium on Water in Mineral Processing, this book shares the insights of dozens of respected experts from industry and academia. A significant portion of the content is devoted to saline solutions and processing with sea water.